Gender Bias and Empowering Women in Short Film “Padanan”: Bias Gender dan Pemberdayaan Perempuan dalam Film Pendek “Padanan” - Raihana, Yasmin; Fikri, M. Andi (House of Wisdom: Journal on Library and Information Sciences, 2025)
This study aims to identify, explain, and analyze different behaviors towards genders. The short film "Padanan" aims to address and prevent implicit gender bias behaviors portrayed in each scene. The research methodology employed is qualitative, focusing on describing social phenomena through in-depth analysis supported by relevant theories with data collection conducted through documentary studies, particularly the analysis of the short film "Padanan" available on the Instagram account @yasminnrhn. The research findings reveal five types of gender bias actions. Firstly, marginalization, which restricts individuals perceived as weak in social status. Secondly, sexual violence, categorized into three levels: normalization, degrading, and assault. Thirdly, stereotypes, involving gender labeling normalized by society, such as prohibiting women from leading and judging men for showing weakness. Fourthly, double burden, arising from normalized marginalization and stereotypes, resulting in job imbalances between genders. Lastly, subordination, indicating the belief that women's position is lower than men's. Highlights: Types of Gender Bias: Five forms of gender bias identified: marginalization, sexual violence, stereotypes, double burden, and subordination. Film Focus: "Padanan" illustrates and aims to prevent implicit gender bias through its scenes. Methodology: Qualitative approach using documentary studies and analysis of the film on Instagram. Keywords: Gender Bias, Women Empowerment, Padanan Film